Observation of the decays [lambda]0b→[chi]c1pK− and [lambda]0b→[chi]c2pK− - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2017)
The first observation of the decays Λ0b→χc1pK− and Λ0b→χc2pK− is reported using a data sample corresponding to an integrated luminosity of 3.0 fb−1, collected by the LHCb experiment in pp collisions at center-of-mass energies of 7 and 8 TeV. The following ratios of branching fractions are measured: B(Λ0b→χc1pK−)B(Λ0b→J/ψpK−)=0.242±0.014±0.013±0.009,B(Λ0b→χc2pK−)B(Λ0b→J/ψpK−)=0.248±0.020±0.014±0.009,B(Λ0b→χc2pK−)B(Λ0b→χc1pK−)=1.02±0.10±0.02±0.05,where the first uncertainty is statistical, the second systematic, and the third due to the uncertainty on the branching fractions of the χc1→J/ψγ and χc2→J/ψγ decays. Using both decay modes, the mass of the Λ0b baryon is also measured to be mΛ0b=5619.44±0.28±0.26 MeV/c2, where the first and second uncertainties are statistical and systematic, respectively.